Formulasi dan Uji Stabilitas Fisik Masker Gel Peel Off Ekstrak Metanol Alga Merah (Eucheuma cottonii) Variasi Konsentrasi Polivinil Alkohol (Film Forming) - Arifin , Arfiani; Ida , Nur; Sureda (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2025)
Red algae is a type of seaweed that has many biological activities, including its role as an antioxidant. The purpose of this study was to formulate a peel off gel mask preparation of methanol extract of red algae (Eucheuma cottonii) that meets the requirements of the physical stability test. The extraction method used was maceration using methanol solvent. Formulations were made using variations in Polivinil Alkohol (PVA) concentration FI (8%), FII (9%) and FIII (10%). Physical stability testing included organoleptic test, homogeneity test, pH test, spreadability test, adhesion test and dry time test conducted before and after storage at 15OC and 40˚C for 6 cycles (24 hours) using a climatic chamber. Based on the results of the study, it was found that the peel off gel mask preparations with PVA concentrations FI (8%), FII (9%), and FIII (10%) met the requirements of the physical stability test before and after storage.